Pengembangan Media Oper Tembak Dalam Pembelajaran Permainan Sepakbola Untuk Siswa Kelas V Sekolah Dasar - Isna Nafida; Martin Sudarmono; Sulaiman; Bhayu Billiandri (Indonesian Journal for Physical Education and Sport, 2024)
The background of this study is the lack of enthusiasm of female students towards soccer learning. The lack of supporting facilities and infrastructure is a major factor in learning and the lack of teacher creativity in innovating learning media. The problem in this study is "How is the form of media development of Pass Shoot cards in learning soccer games for grade V elementary school students". This research is development research or Research and Development (R&D) with the stages of research and development consisting of 1) potential and problem formulation, 2) data collection, 3) product design, 4) design validation (one game expert and two learning experts), 5) design revision, 6) small scale trial (12 students), 7) product revision, 8) large scale trial (57 students), 9) product revision, 10) production which produces OMBAK (pass shoot) card media for soccer games in elementary schools. The results of product validation in the study resulted in a value on the soccer game expert of 73.33%, learning expert 1 of 85%, and learning expert 2 of 96.66%. After the product was revised by experts and declared feasible to be tested and used. After that the product was tested on a large scale with the average result getting a score of 97.07% (Very Good). The results of the conclusion from the research carried out that the OMBAK (pass shoot) card media can be used as a means of supporting learning soccer games. Suggestions for PJOK teachers at school to be able to utilize this media can help students to be more enthusiastic about participating in learning at school